Chronic Background Radiation Correlates With Sperm Swimming Endurance in Bank Voles From Chernobyl - Kivisaari, Kati; Calhim, Sara; Lehmann, Philipp; Boratyński, Zbyszek; Mousseau, Timothy A.; Møller, Anders P.; Mappes, Tapio (Frontiers in Ecology and Evolution, 2022)
Sperm quantity and quality are key features explaining intra- and interspecific variation in male reproductive success. Spermatogenesis is sensitive to ionizing radiation and laboratory studies investigating acute effects of ionizing radiation have indeed found negative effects of radiation on sperm quantity and quality. In nature, levels of natural background radiation vary dramatically, and chronic effects of low-level background radiation exposure on spermatogenesis are poorly understood. The Chernobyl region offers a unique research opportunity for investigating effects of chronic low-level ionizing radiation on reproductive properties of wild organisms. We captured male bank voles (Myodes glareolus) from 24 locations in the Chernobyl exclusion zone in 2011 and 2015 and collected information on sperm morphology and kinetics. The dataset is limited in size and there overall was a relatively weak correlation between background radiation and sperm quality. Still, some correlations are worth discussing. First, mid-piece segments of spermatozoa tended to be smaller in bank vole males from areas with elevated background radiation levels. Second, we demonstrated a significant positive relationship between background radiation dose rates and the proportion of static spermatozoa among males within and among study locations after 10 as well as 60 minutes of incubation. Our results provide novel evidence of damaging effects of low dose ionizing radiation on sperm performance in wild rodent populations, and highlight that this topic requires further study across the natural gradients of background radiation that exist in nature.